(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
The history of argument theories is, in general, the history of the evolution of the use of structures, procedures and resources. Probably due to that, some unresolved problems such as periodization, conceptualization, descriptor indices, and whether we should talk about one or several theories built upon different contributions along the tradition, still remain. In this paper, we state these problems, propose an extension to one of the classical periodization schemes, and focus primarily on presenting some relevant elements in order to draw a picture of the first of these periods known as ―foundational‖.